Modeling of drug release from a bioresorbable polymer matrix system - Yasir M.; Puri D.; Arumugam M.; Gobena W.G.; Wondabo M.H.; Roshan S.; Noorulla K.M. (My University, 2025)
Dissolution followed by drug release is the prime step after the administration of a solid oral delivery system to ensure the proper drug concentration in the blood or at the action site/receptor. This is due to only the dissolved drug being able to diffuse through biological barriers like the mucosa of the gastrointestinal tract. Controlled-release formulations are made up of various types of polymers such as biodegradable/bioresorbable polymers which further influence the release of drugs and can improve patient compliance through reducing side effects by extending the dosing interval and targeting efficiency. Several pharmaceutical products made up of biodegradable polymers have become available and have been approved by the FDA in order to enable the effective and safe delivery of drugs like hormones, proteins, antibiotics, antitumors, and several other drugs. Despite the huge diversity in drug-delivery systems and the applicability of different biodegradable polymers for their design, diffusion is involved in almost all types of release processes. Over more than 50 years, scientists have developed various drug-delivery systems/drug carriers and studied their properties to acclimatize them to the release environment. Additionally, drug/carrier association behaviors have been thoroughly investigated, and the release kinetics have been modeled in accordance with the systemic phenomena. In the literature, researchers have reported a number of mathematical models to describe the mechanisms and kinetics of drug release from the formulation matrix. This chapter describes biodegradable polymers, diffusion law, various types of model used for assessing drug-release kinetics, etc. © 2024 Elsevier Ltd. All rights reserved.